PREVALENCE OF OSTEOARTHRITIS IN RUSSIA: REGIONAL ASPECTS OF TRENDS IN STATISTICAL PARAMETERS DURING 2011–2016 - M. A. Kabalyk (Научно-практическая ревматология)
Recent demographic changes caused by labor migration and by the larger number of retirement-aged people, as well as unstable economic conditions are the reason for analyzing the incidence of osteoarthritis (OA) in the adult population of the Russian Federation in the light of changing socioeconomic factors. Objective: to analyze the incidence of OA in the regions of the Russian Federation in terms of key socioeconomic factors. Material and methods. Trends in OA prevalence and incidence were retrospectively analyzed using the data of annual statistical reports of the Ministry of Health of Russia (Form No. 12) in the period 2011–2016. The above parameters were studied among three population cohorts: adult, able-bodied, and retirement-aged (pensioners) people. Data on the execution of consolidated budgets of the regions of the Russian Federation, territorial compulsory health insurance funds (TCHIFs) were analyzed to identify substantial socioeconomic factors influencing the trends in statistical parameters. The findings were subjected to a comparative analysis of these parameters for Russia as a whole, 85 regions, and 8 federal districts. Results and discussion. During the period from 2011 to 2016, the prevalence of OA in Russia increased from 32.2 per 1,000 population in 2011 to 35.7 in 2016. The highest prevalence of OA is observed among the retirement-aged population and averages 33.2% of the number of registered patients per the total population in this age group during 6-year follow-ups. The maximum prevalence is seen in the retirement-aged population (70.4 per 1,000 corresponding age population; which is more than 3.8 times greater than that in the able-bodied one). There is a steady increase in the prevalence and incidence of OA in the population of Russia as a whole. According to official statistics, patients with OA make up one quarter of all patients with musculoskeletal system diseases and OA is detected in 4% of the entire adult population. Over 20 years, the number of patients with OA increased by 260%. The investigation has shown that the population’s income growth is associated with lower incidence and prevalence rates among pensioners. During 6 years, there is a decline in budget funding for health care in 30 regions of Russia. The share of expenditures in the consolidated regional budgets has been established to be directly associated with the incidence and morbidity of OA. There was an average 183% increase in the expenditures of TCHIFs in Russia. The expenditures of TCHIFs in the regions were directly related to the higher incidence of OA among adults and pensioners, but were unassociated with those among the able-bodied population.